2017
DOI: 10.1093/nar/gkx891
|View full text |Cite
|
Sign up to set email alerts
|

exoRBase: a database of circRNA, lncRNA and mRNA in human blood exosomes

Abstract: Exosomes, which are nanosized endocytic vesicles that are secreted by most cells, contain an abundant cargo of different RNA species that can modulate the behavior of recipient cells and may be used as circulating biomarkers for diseases. Here, we develop a web-accessible database (http://www.exoRBase.org), exoRBase, which is a repository of circular RNA (circRNA), long non-coding RNA (lncRNA) and messenger RNA (mRNA) derived from RNA-seq data analyses of human blood exosomes. Experimental validations from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
334
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(345 citation statements)
references
References 26 publications
1
334
0
2
Order By: Relevance
“…69 Additionally, many recent studies have examined noncoding RNAs in exosomes, which can carry a variety of noncoding RNAs to receptor cells and facilitate communication between nonadjacent cells. [71][72][73] Exosomes can participate in the occurrence and development of cancer invasion, and the high expression of circRNAs observed in the peripheral blood of patients with cancer suggested that the target circRNA might be protected by exosomes or extracellular vesicles. Further studies are needed to assess these potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…69 Additionally, many recent studies have examined noncoding RNAs in exosomes, which can carry a variety of noncoding RNAs to receptor cells and facilitate communication between nonadjacent cells. [71][72][73] Exosomes can participate in the occurrence and development of cancer invasion, and the high expression of circRNAs observed in the peripheral blood of patients with cancer suggested that the target circRNA might be protected by exosomes or extracellular vesicles. Further studies are needed to assess these potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…exoRBase [54], containing circRNA, lncRNA and mRNA, which were derived from RNA-seq data analyses of human blood exosomes. It could do a lot to the circRNA studies by providing users with the detailed genomic and protein-coding information of each cir-cRNA.…”
Section: Exorbasementioning
confidence: 99%
“…At the time of writing, we were able to find 11 online databases that include circRNAs, have a web-based interface and are easily reachable from the links provided in the corresponding papers (Table 1): BBBomics, 20 circ2Traits, 21 circBase, 22 circInteractome, 23,24 circNet, 25 circRNADb, 26 CSCD, 27 exorBase, 28 PlantcircBase, 29 Soma-miR, 30 TSCD. 31 A recent study by Ying Xu provides an overview of the major databases currently available.…”
Section: Databasesmentioning
confidence: 99%